ANALISIS KEMAMPUAN MEMAHAMI MASALAH MATEMATIKA PADA SOAL CERITA DITINJAU DARI GAYA BERPIKIR SEKUENSIAL KONKRET - YULIANI, ASKA MUTA; SAPUTRA, ADI; SUSILOWATI, RINA (Universitas Mahasaraswati K. Mataram, 2023)
This research aims to analyze how students' ability to understand problems in story problems is seen from the concrete sequential thinking (SK) style. The research subjects consisted of three class VII students at SMPN 5 Moyo Hilir who had a concrete sequential thinking style that came from their respective abilities in understanding low, medium, and high categories of mathematical problems. The research approach used is descriptive qualitative with data collection methods including questionnaires, tests, and interviews. Questionnaires are used to classify students' thinking styles. Students who fall into the SK thinking style category are given a written test to determine their ability to understand students' problems. Written test results are confirmed through interviews with students. The research results showed that students with a high and moderate ability to understand problems answered questions systematically and in detail according to the characteristics of SK's thinking style. Students with a high ability to understand problems can determine each element that is known and ask about the problem precisely and clearly. Students with the ability to understand the problem still have writing errors but can understand the problem correctly. Students with a low ability to understand problems are not able to understand all the questions correctly due to a lack of understanding of concepts related to social arithmetic material. The process of problem solving is not systematic and irregular, so it does not match the characteristics of a concrete, sequential thinking style.